Strategic Policy Response to Climate Change in the Philippines Vol. 2: Exploring How Climate Change Policies are Translated into Local Actions in the Agriculture Sector - Rebugio, Lucrecio; Ilao, Susan Sandra; Burgos, Bessie; Rogel, Carmen Nyhria; Wassmann, Reiner; Sander, Björn Ole (SEARCA and IRRI, 2018)
This volume provides relevant information on the Philippine climate change policy response strategy in agriculture, with focus on local implementation of climate change policies. Specifically, it describes the local institutional setting for climate change policy implementation in agriculture, the dynamics by which climate change policies in agriculture are translated into meaningful actions and desired changes, and the bottlenecks to effective climate change policy implementation in agriculture at the local level. This volume highlights the exploratory case study on climate change policy implementation in agriculture conducted in Central Luzon, Philippines.